Oxidative stress response to aluminum oxide (Al2O3) nanoparticles in Triticum aestivum - VARDAR, FİLİZ (SPRINGER, 2018)
The development of nanotechnologies has increased the amount of manufactured metal oxide nanoparticles in the environment. In the view of nanoparticle dispersion to the environment, assessment of their toxicity becomes very crucial. Aluminum oxide (Al2O3) nanoparticles have wide range of use in industry as well as personal care products. The aim of this study was to evaluate the dose dependent effects of 13-nm-sized Al2O3 nanoparticles on wheat correlating with the appearance of enzymatic and non-enzymatic antioxidant defense response. Wheat roots were exposed to different concentrations of Al2O3 nanoparticles (5, 25 and 50 mg mL(-1)) for 96 h. The effects of Al2O3 nanoparticles were studied using different parameters such as H2O2 content, superoxide dismutase and catalase activity, lipid peroxidation, total proline, photosynthetic pigment and anthocyanin content. The results indicated that while Al2O3 nanoparticles caused a dose dependent increase in H2O2 content, superoxide dismutase activity, lipid peroxidation and proline contents, the catalase activity was decreased in compare the control. Moreover, total chlorophyll, chlorophyll a, carotenoids and anthocyanin contents reduced in the highest concentration 50 mg mL(-1). In conclusion, Al2O3 nanoparticles caused oxidative stress in wheat after 96 h.
Keywords: Triticum aestivum; Aluminum oxide nanoparticles; Enzymatic antioxidants; Non-enzymatic antioxidants; Oxidative stress; Photosynthetic pigments; SALICYLIC-ACID; SUPEROXIDE-DISMUTASE; ARABIDOPSIS-THALIANA; L. SEEDLINGS; PLANTS; EXPOSURE; LEAVES; LIGHT; ANTIOXIDANTS; PEROXIDASE